Investigating the effect of educational interventions on maternal competence: A systematic review and meta-analysis - Maryam Fasanghari; Afsaneh Keramat (Wolters Kluwer Medknow Publications, 2023)
There have been many studies on maternal competence, but in the studies conducted in this field, different methods have been applied to educate mothers on maternal competence, which do not have a unified approach. This study aims to investigate the effect of educational interventions on maternal competence using a meta-analysis method. In this meta-analysis, a search was made in MEDLINE, CINAHL, PubMed, Scopus, Proquest, Google scholar, SID, and Magiran databases using Mesh and non-Mesh keywords between January 1992 and September 2022. The inclusion criteria included: Studies in which educational and counseling interventions on maternal competence have been investigated, studies that have used the Parenting Sense of Competence Scale (PSOC), RCT or interventional studies, participants who were primiparous women, articles that were published in English and Farsi, studies that reported sample size, mean and standard deviation of maternal competence scores in the intervention and control groups, and studies that scored at least 3 on the Jadad scale. Data were analyzed using Review Manager 5 (RevMan 5.3). In this meta-analysis and systematic review, finally, seven articles met the criteria for entering the research. The number of samples in the intervention group was 430 and in the control group was 429. The average maternal competence score with a 95% confidence interval was 3.51. This meta-analysis showed that educational interventions during pregnancy and after delivery could affect improving the competence of primiparous mothers. Education has increased the maternal competence score in the intervention group by 3.51 units compared to the control group.